Website Development as a Media Promotion of Tourism Destinations in Manokwari Regency - Talumepa, Gabriel; Nainggolan, Nelson; Takaendengan, Mahardika Inra (Universitas Teknokrat Indonesia, 2025)
Manokwari Regency has many tourist attractions but the lack of promotion causes the tourist attractions there to be less well-known. As technology develops, online tourism promotion is becoming increasingly important so that more people can get to know the tourist destinations in Manokwari Regency. One way to answer this challenge is to build an interactive and informative web-based information system. The Rapid Application Development (RAD) method was chosen because this method allows the system to be created quickly and can be improved according to user input. The development process begins with a needs analysis through observation and interviews with related parties, such as tourism businesses, tourists, and the local community. The information collected was used as the basis for creating the initial design of the system. Next, a system design is carried out which includes making a simple and easy-to-understand Unified Modeling Language (UML), as well as designing a database that can manage tourist destination information data. This website provides complete information about tourist destinations, travel routes, galleries, descriptions of tourist attractions and provides English features to facilitate international tourists. The test results using the Black Box Testing method show that all features run as expected. The implementation of this system is expected to provide convenience for tourists in accessing tourist information, increasing the attractiveness of regional tourism, and supporting the promotion of tourist destinations. Thus, this research contributes to utilizing digital technology to improve the tourism sector in Manokwari Regency.